Residências do setor Central: por que preservá-las? - Barros, Renata Lima (2019)
The deterioration of Heritage Assets is concerning. The lack of initiatives that pursuit its appreciation and preservation causes its loss. Our assets are part of our identity. They tell a story from the past and they are our form of communication with the future generations. What can be done for its preservation? In Brazil, a legislation specific to preserve Brazilian heritage assets is not enough. The preservation is not only a matter of the Brazilian Public Power, there needs to be social involvement. Given the importance of the relationship between society and the Heritage Assets, this dissertation will study some of the remaining historical residences in the Central Region of Goiânia, Brazil. Four of the residential buildings were selected and studied to better understand how people interact with these assets. The research includes architectural and urban analysis and importantly interviews with the owners. It was necessary to understand the value of these assets that go beyond the historical and architectural pointed by scholars. The owners add to the Assets and will affect its preservation process.